Odpowiedzi

  • Użytkownik Zadane
2010-04-06T19:14:29+02:00
3(x-1)=0
3x-3=0
3x=3/:3
x=1

-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:(-6)
x=-5

-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5

0,2x+0,3=-0,5
0,2x=-0,5-0,3
0,2x=-0,8/:0,2
x=-4

0,4+0,25x=-2
0,25x=-2-0,4
0,25x=-2,4/:0,25
x=-9,6

2,1-0,3x=0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1/:(-0,7)
x=3

-1,5x-3=0,2x+6
-1,5x-0,2x=6+3
-1,7x=9/:(-1,7)
x=-90/17
Najlepsza Odpowiedź!
2010-04-06T19:15:32+02:00
3(x-1)=0
3x-3 = 0
3x= 3
x = 1

-6(x+1)=24
-6x -6 = 24
-6x = 24 +6
-6x = 30
x = - 5


-7(x-2)=3x-1

-7x + 14 = 3x-1

-7x+14 - 3x+1 = 0

-10 x = -15

x =1,5

4(x-1)=6(1+x)

4x+4 = 6 +6x
4x-6x=6+4
-2x=10
x=-5

0,2x+0,3=-0,5
0,2x = -0,5 - 0,3
0,2x = -0,8
x = -4

0,4+0,25x=-2
0,25x = -2 - 0,4
0,25x = -2,4
x = - 9,6

2,1-0,3x=0,4x
2,1 = 0,4x +0,3x
2,1 = 0,7x
3 = x


-1,5x-3=0,2x+6
-1,5x - 0,2x = 6+3
-1,7x = 9
- 1 7/10 x = 9
-17/10 x = 9

x = 9 * ( - 10/17)

x = - 90 /17